Financial Attitudes and Behaviors of Internal Medicine and Internal Medicine–Pediatrics Residents - Wong, Rachel (J Grad Med Educ, 2018)
BACKGROUND: Residents graduate from medical school with increasing levels of debt and also may possess poor financial knowledge and practices. Prior studies have assessed resident financial knowledge and interest in financial education, yet additional information regarding their attitudes about personal finance and financial planning could be essential for the development of relevant curricula. OBJECTIVE: We assessed baseline financial attitudes and planning behaviors of internal medicine and internal medicine–pediatrics residents in 3 geographically diverse academic programs. METHODS: A modified version of the Financial Industry Regulatory Authority National Financial Capability survey was administered anonymously to residents in 3 programs in spring 2017. Outcomes included levels of educational debt, positive financial planning behaviors, perception of finances and debt, and education about personal finance. RESULTS: Response rate was 62% (184 of 298). Rates of educational debt were high, with 81% (149 of 184) of respondents reporting educational debt, and the majority owing more than $100,000. Residents' financial practices were variable, and residents could be grouped into 1 of 3 categories—concerned-engaged, concerned-unengaged, and unconcerned-unengaged—based on their engagement with debt and financial management. Residents with high debt (> $250,000) had a bimodal distribution of respondents who strongly agreed and those who strongly disagreed they were concerned about debt. CONCLUSIONS: Resident financial attitudes and practices are variable, ranging from highly engaged residents actively managing their financial wellness to unengaged residents who have low concern, despite high educational debt.